2013
DOI: 10.1111/jhn.12151
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of meal replacements with an isocaloric reduced‐fat diet on nutrient intake and lower urinary tract symptoms in obese men

Abstract: Weight loss as a result of CD or MR had similar efficacy in relieving LUTS. MR produced greater reductions in fat intake, adiposity and storage LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…Our findings are in contrast to prior reports [6,7,35,36] where improvements in the SDI or IPSS occurred following weight losses of 2-6-12.3 kg over 8–52 weeks. We note that an improvement in the storage LUTS score occurred for those with the presence of features of lower urinary tract symptoms relating to storage symptoms at baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in contrast to prior reports [6,7,35,36] where improvements in the SDI or IPSS occurred following weight losses of 2-6-12.3 kg over 8–52 weeks. We note that an improvement in the storage LUTS score occurred for those with the presence of features of lower urinary tract symptoms relating to storage symptoms at baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…Fourteen studies were conducted in people who were overweight but with no specific clinical condition, five in people with type 2 diabetes, two in participants with metabolic syndrome or impaired glucose regulation, one in men with type 2 diabetes and erectile dysfunction, and one in adults with developmental disabilities and obesity …”
Section: Resultsmentioning
confidence: 99%
“…In 15 studies (65%), the MR used consisted of specially formulated shakes, soups, or bars . In four studies (17%), the MR consisted of prepackaged portion‐controlled meals which participants reconstituted or cooked at home, and in four studies (17%), the MR was a combination of prepackaged portion‐controlled meals and specially formulated shakes, soups, or bars …”
Section: Resultsmentioning
confidence: 99%
“…Physical adverse effects were reported in only a single study in which participants received very-low-calorie ketogenic diets, and these effects ceased when a normal diet was resumed. Only a single RCT [48] assessed mental health outcomes associated with dietary interventions for weight loss. This study compared the meal replacement Optifast to a conventional reduced-fat diet, and reported significant quality of life improvements in both groups.…”
Section: Resultsmentioning
confidence: 99%